Boosting radical innovativeness through start-up acquisitions: the role of decision autonomy and structural integration - Andrea Greven; Denise Fischer-Kreer; David Bendig; Stefan Pöhler; Malte Brettel (R&D Management, 2023)
Since start-ups often own cutting-edge technology and knowledge, acquiring a start-up can provide buyers with a unique opportunity to boost their radical innovativeness. As a result, start-up acquisitions have increasingly gained importance. Acquirers, however, face difficult decisions on target autonomy and integration, which often constitute a dilemma. We analyzed survey data from 118 M&A and integration managers in charge of corporate start-up acquisitions. Our results show that a start-up's decision-making autonomy supports acquirer's radical innovativeness. The structural integration of the target reinforces the positive effect of decision autonomy. Our work with the focus on post-merger integration and the start-up context contributes to M&A literature in several ways. We uncover a hybrid integration approach, showing that a combination of high target decision autonomy and the full absorption (i.e., structural integration) of the start-up by the acquiring organization is most beneficial for acquirer's radical innovativeness.
Keywords: 650